Inevitáveis violações de simetria em cálculos perturbativos de TQC\'s em dimensão D=1+1 - Ebani, Luciana (2015)
A alternative strategy to the traditional regularization methods, developed to perform manipulations and calculations involving perturbative amplitudes containing divergences, coming from Quantum Field Theories, which we call Predictive Perturbative Calculation, is applied in an investigation in order to check the possibility of consistency in this kind of calculation. The level of approximation is the 1-loop, in the context of a model containing different species of massive fermions of spin 1/2, interacting with bosons of spin 0 and spin 1, having even and odd parities and formulated in the space-time dimension D = 1 + 1. It is considered the explicit calculation of the amplitudes, the verification of relations among the Green functions and the associated Ward identities as well as the possibility of ambiguities. Low-energy theorems are also considered. At the end it is presented the conclusions of the investigation, which reveal that it is not possible to obtain consistency in the usual context, where the perturbative amplitudes are assumed as regularized amounts. Violations in symmetry relations are identified, as well as in low energy limits, even in non-anomalous amplitudes, in a way completely similar to those identified in anomalous amplitudes, in traditional methods. The conclusions reveal that it is necessary to find a new interpretation for the perturbative amplitudes in order to obtain the desired consistency.